2017
DOI: 10.1038/srep44021
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomics Reveals HMGA1, a CK2 Substrate, as a Drug-Resistant Target in Non-Small Cell Lung Cancer

Abstract: Although EGFR tyrosine kinase inhibitors (TKIs) have demonstrated good efficacy in non-small-cell lung cancer (NSCLC) patients harboring EGFR mutations, most patients develop intrinsic and acquired resistance. We quantitatively profiled the phosphoproteome and proteome of drug-sensitive and drug-resistant NSCLC cells under gefitinib treatment. The construction of a dose-dependent responsive kinase-substrate network of 1548 phosphoproteins and 3834 proteins revealed CK2-centric modules as the dominant core netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 60 publications
(64 reference statements)
2
29
0
Order By: Relevance
“…We identified HMGA1 S102 as a hyperphosphorylated site in cells expressing ectopic SRMS (Additional file 2 : Table S1). HMGA1 S102 is a target site for phosphorylation by CK2 [ 49 , 50 ] and studies have shown that the hyperphosphorylation of HMGA1 S102 impairs the DNA-binding ability of the protein [ 51 , 52 ]. The dissociation of HMGA1 from the DNA in turn promotes efficient DNA repair, presumably by allowing various DNA repair factors to be recruited to the sites of DNA lesions, as reported previously [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…We identified HMGA1 S102 as a hyperphosphorylated site in cells expressing ectopic SRMS (Additional file 2 : Table S1). HMGA1 S102 is a target site for phosphorylation by CK2 [ 49 , 50 ] and studies have shown that the hyperphosphorylation of HMGA1 S102 impairs the DNA-binding ability of the protein [ 51 , 52 ]. The dissociation of HMGA1 from the DNA in turn promotes efficient DNA repair, presumably by allowing various DNA repair factors to be recruited to the sites of DNA lesions, as reported previously [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…These techniques have been successful for a large number of resistance mechanisms (11,4245), but can fail to identify epigenetic/non-genomic mechanisms of resistance. As an additional strategy, several groups have used MS-based phosphoproteomics or RTK-arrays to identify signaling based mechanisms of resistance (16,36,4648). MS-based phosphoproteomics has typically been applied to in vitro cell culture following long-term treatment and development of resistance, and has been successful in identifying some common mechanisms of resistance, many of which have been validated in vivo (in cell line xenografts or patient derived xenografts).…”
Section: Discussionmentioning
confidence: 99%
“…This category contains the two HSP90 isoforms (HSP90AA1 and HSP90AB1), which harbor PTM sites involved in the regulation of the chaperone activity (Mollapour and Neckers, 2012). These isoforms are known to be phosphorylated at Ser263 and Ser255, respectively (Hu et al, 2015; Wang et al, 2017), within the CK2 phosphorylation motif (S-X-X-E) that is crucial for protein activity. In particular, phosphorylation at Ser255 is required for the activation of MAPK/ERK pathway.…”
Section: Resultsmentioning
confidence: 99%